EMOTIONAL INTELLIGENCE AND INTERPERSONAL RELATIONS AMONG UNIVERSITY UPGRADING (GRADE V) TEACHER STUDENTS - Waiswa, Helen Christine Amongin; Baguma, Peter K.; Oonyu, Joseph (International Journal of Psychology, 2020)
Purpose: This paper examined the relationship between emotional intelligence (EI) and interpersonal relations (IR) among upgrading university teacher students at Makerere University (MAK) and Uganda Christian University (UCU). While the curricula and syllabi in the Teacher Education programmes in Uganda do not clearly stipulate EI as a vital and critical factor, literature shows that EI is responsible for 80% of the success in our lives. IR enables teacher students perform better, be emotionally well adjusted to perform other activities besides teaching, as well as professionally deal with the community within the school. Methodology: The study used mixed methodology, DCM SPSS 22 data analysis, a sample of 434 Grade V teacher students randomly sampled for qualitative survey design and 75 purposively selected participants for qualitative design, with The ability model of Emotional Intelligence (Mayer et al., 2016). Findings: Overall emotional intelligence was not significantly related to quality of interpersonal relations (r = .08, p > .05). Similarly, all aspects of emotional intelligence were not significantly related to quality of interpersonal relations. Qualitative results show that some participants were not clear about the difference between EI and cognitive intelligence. EI is positively correlated to IR. For better IR, one needs a high level of EI. Conclusively, although the quantitative data showed no significance between EI and IR qualitative data indicated results to the contrary. Subsequently, the teaching of EI especially at the university level is new to the education curriculum of Uganda. Unique contribution to theory, practice and policy: Most teacher students had not heard of EI. Thus, there is need to put emphasis on IR at all levels of education and to deliberately include EI in the curriculum. Most previous scholarship on EI did not use mixed methodology. This is the first study to use the ability model of EI (Mayer et al., 2016), in an educational research using mixed methods. The study recommends more research, teaching and training in EI and IR in the educational fraternity. Further research needs to be done using the ability model of EI.